2015
DOI: 10.1128/jb.00291-15
|View full text |Cite
|
Sign up to set email alerts
|

Positive Effect of Carbon Sources on Natural Transformation in Escherichia coli: Role of Low-Level Cyclic AMP (cAMP)-cAMP Receptor Protein in the Derepression of rpoS

Abstract: Natural plasmid transformation of Escherichia coli is a complex process that occurs strictly on agar plates and requires the global stress response factor S . Here, we showed that additional carbon sources could significantly enhance the transformability of E. coli. Inactivation of phosphotransferase system genes (ptsH, ptsG, and crr) caused an increase in the transformation frequency, and the addition of cyclic AMP (cAMP) neutralized the promotional effect of carbon sources. This implies a negative role of cA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 41 publications
(40 reference statements)
0
21
0
Order By: Relevance
“…cAMP is synthesized when the cell is using secondary carbon sources (rather than glucose), and the global transcriptional regulator CRP, in complex with cAMP, positively regulates the genes necessary for using these less-favored carbon sources. A number of studies show higher levels of RpoS early in exponential phase in the absence of cAMP and CRP (3,17,23,24), suggesting negative transcriptional regulation by CRP/cAMP, and based on these studies, EcoCyc currently shows the rpoS promoter as negatively regulated by CRP (25). However, other studies show positive effects of cAMP and CRP (26), and muta- JBC REVIEWS: Bacterial general stress responses tions in the suggested CRP-binding sites upstream and downstream of the major rpoS promoter significantly reduced RpoS expression (23), providing compelling evidence for an important positive role for CRP for RpoS transcription.…”
Section: Transcriptional Regulationmentioning
confidence: 99%
“…cAMP is synthesized when the cell is using secondary carbon sources (rather than glucose), and the global transcriptional regulator CRP, in complex with cAMP, positively regulates the genes necessary for using these less-favored carbon sources. A number of studies show higher levels of RpoS early in exponential phase in the absence of cAMP and CRP (3,17,23,24), suggesting negative transcriptional regulation by CRP/cAMP, and based on these studies, EcoCyc currently shows the rpoS promoter as negatively regulated by CRP (25). However, other studies show positive effects of cAMP and CRP (26), and muta- JBC REVIEWS: Bacterial general stress responses tions in the suggested CRP-binding sites upstream and downstream of the major rpoS promoter significantly reduced RpoS expression (23), providing compelling evidence for an important positive role for CRP for RpoS transcription.…”
Section: Transcriptional Regulationmentioning
confidence: 99%
“…In a few Gram‐negative bacterial species, it was found that carbon catabolite repression (CCR) is involved in the regulatory network governing natural competence and transformation (Lo Scrudato and Blokesch, ; Guo et al , ; Yang and Lan, ). The CCR mechanism is widely employed by bacteria to repress the utilization of non‐preferred carbohydrates such as galactose and mannose (Gorke and Stulke, ; Rojo, ).…”
Section: Introductionmentioning
confidence: 99%
“…Second, an OM protein, OmpA, plays opposite roles in natural and chemical transformation of E. coli : it promotes chemical transformation but suppresses natural transformation ( Sun et al, 2013 ). Third, exponentially growing E. coli cells are often employed for preparing chemically competent cells with the highest efficiency, and chemical transformation occurs in a liquid, whereas the natural transformation of stationary-phase E. coli cells is regulated by the transcriptional regulator RpoS and the cyclic AMP (cAMP) – cAMP receptor protein (CRP), and these cells can acquire exogenous DNA exclusively on agar plates ( Zhang et al, 2012 ; Guo et al, 2015 ). The functions of RpoS or the cAMP-CRP complex in the chemical transformation of E. coli have not been found.…”
Section: The Uptake Of Dsdna In E Colimentioning
confidence: 99%